2021
DOI: 10.1111/aogs.14087
|View full text |Cite
|
Sign up to set email alerts
|

Is abdominal hysterectomy still the surgery of choice in sub‐Saharan Africa?

Abstract: A trend toward minimally invasive surgery is increasing worldwide. However, reports on the extent and the role of vaginal or laparoscopic hysterectomy in benign gynecologic surgery in sub‐Saharan Africa are scarce. Our commentary aims to highlight the existing gaps and potential barriers to implementation of vaginal or laparoscopic hysterectomy and suggests how to introduce and expand minimally invasive gynecologic surgery in this region. Little documentation exists in the literature to account for the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…There was no statistical significant difference between the three studied groups regarding ASA (P1, P2, and P3 > 0.05). Figure (1) showed that there was no statistically significant difference between group C with group D2 and between group D2 with D4 at different periods of follow up (P1 & P3 > 0.05), while there was statistical significant difference between group C and D4 from period 30 min I.O to 12 hr. postoperative (P2 < 0.05) regarding heart rate.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…There was no statistical significant difference between the three studied groups regarding ASA (P1, P2, and P3 > 0.05). Figure (1) showed that there was no statistically significant difference between group C with group D2 and between group D2 with D4 at different periods of follow up (P1 & P3 > 0.05), while there was statistical significant difference between group C and D4 from period 30 min I.O to 12 hr. postoperative (P2 < 0.05) regarding heart rate.…”
Section: Resultsmentioning
confidence: 88%
“…Table (1) showed that age in group C ranged from 26-63 years with mean value of 46.07 ± 11.12, in group D2 ranged from 27-63 years with mean value of 44.93 ± 10.76 and in group D4 ranged from 28-65 years with mean value of 42.56 ± 11.79. There was no statistical significant difference between the three studied groups regarding age (P1, P2, and P3 > 0.05).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…One of the most successful hysterectomy registration systems in the world is the Danish Hysterectomy and hysteroscopy database (DHHD) (Since 2003). All Danish women who have undergone an elective hysterectomy, which is recorded directly by the surgeons involved in the treatment and prospectively [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Robot-assisted hysterectomy is the most common approach in the United States of America [115], laparoscopic hysterectomy predominates in Australia [114], Denmark [111] and Taiwan [113], whereas the vaginal approach is customary in Austria [116]. In developing nations, abdominal hysterectomy remains the norm [117].…”
Section: Discussionmentioning
confidence: 99%